Eu vou andar de trem / você vai também: uma viagem pela dinâmica de constituição cultural das crianças de uma turma de 3 anos na Educação Infantil - Lilian Aparecida de Souza (2017)
The aim of this research is to understand the limits and possibilities of social interaction for 3 - year - old childrens agency in a public early childhood e ducation institution (UMEI), in Belo Horizonte, Brazil. The process of data construction and analysis is based on approaches of the ethnography in Education, in works of the Cultural - Historical Psychology as well as those of the Sociology of Childhood. The data were constructed from observations; annotations in the field diary; video recordings of the class routine; audio recordings of semi - structured interviews with children, with teachers, with the pedagogical managers and with the families of the children; and phot ographs taken by children or requested by them. The data shed light on the complexity of the dynamics of developmental and cultural constitution of the children, triggered by the social interactions that they construct daily in the early childho od education institution with their peers and teachers. The analyses demonstrated that the interactions constitute the central axis from which the cultural practices of the group are (re) produced, appropriated and modified. It was verified that the observ ation of peer culture allows for a better apprehension of these dynamics, once the actions and interactions built during play, especially pretend play, are representative of how children are developing as cultural beings. The analysis of the data revealed meaningful aspects of the cultural practices of the group: collective action, friendship, gender issues, crying, body language, verbally shared senses and meanings, appropriation of institutional culture, imposition and/or negotiation of limits, interpretative reproduction, insertion/participation styles, childrens literature and reading, and racial/ethnic issues. The results also indicated that children were constantly appropriating and relating local cultural practices to global ones. Likewise, it was found that children act as social actors also in the face of limits, transforming them into new possibilities of action. In this sense, the investigation reveals the importance of social interaction and peer culture in early childhood education, as well as the need to observe these moments in order to collaborate with teaching practices that provide children with meaningful experiences that contribute in a constructive way to their development and constitution as cultural beings.